Responses to scoring or conceding the first goal in the NHL - Jones, M. B. (Journal of Quantitative Analysis in Sports, 2011)
In low-scoring sports such as ice hockey or soccer, which team scores the first goal is critically important to game outcome. By the same token, how a team responds to scoring or conceding the first goal is also important. If a team responds well when it concedes the first goal, it may win out in the end. On the other hand, if it handles an initial setback badly, the game may be effectively over. These considerations are knit together in an accounting identity which serves as a scaffold for the present study. Performance after the first goal is controlled by two responses, how well the team which scores the first goal retains its advantage and how well the team which concedes the first goal counters its disadvantage. These two responses are both found to play large roles in which team wins the game and how many goals after the first each one scores. Both responses are highly significant and together account for most of the advantage that the home team enjoys in game outcome. The relation of these results to the frequently encountered idea of momentum is also discussed.